2016
DOI: 10.1103/physrevlett.117.036101
|View full text |Cite
|
Sign up to set email alerts
|

Density and Phase State of a Confined Nonpolar Fluid

Abstract: Measurements of the mean refractive index of a spherelike nonpolar fluid, octamethytetracylclosiloxane (OMCTS), confined between mica sheets, demonstrate direct and conclusive experimental evidence of the absence of a first-order liquid-to-solid phase transition in the fluid when confined, which has been suggested to occur from previous experimental and simulation results. The results also show that the density remains constant throughout confinement, and that the fluid is incompressible. This, along with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…Confinement has also been reported to have a strong impact on the structural relaxation of supercooled liquids [6,11,12] since it restricts the range of accessible length scales, which becomes increasingly important as the glass transition is approached [11]. The effect of confinement on the properties of simple liquids or colloids has, therefore, been carefully studied with experiments [13][14][15][16][17][18][19][20][21][22][23], theory [1,3,7,8,[24][25][26], and simulations [2,[9][10][11][12][27][28][29][30][31][32][33][34]. The results indicate that the rich phenomenology of confined hard spheres indeed accurately applies to liquids and colloids in nanoscopic confinement.…”
Section: Introductionmentioning
confidence: 99%
“…Confinement has also been reported to have a strong impact on the structural relaxation of supercooled liquids [6,11,12] since it restricts the range of accessible length scales, which becomes increasingly important as the glass transition is approached [11]. The effect of confinement on the properties of simple liquids or colloids has, therefore, been carefully studied with experiments [13][14][15][16][17][18][19][20][21][22][23], theory [1,3,7,8,[24][25][26], and simulations [2,[9][10][11][12][27][28][29][30][31][32][33][34]. The results indicate that the rich phenomenology of confined hard spheres indeed accurately applies to liquids and colloids in nanoscopic confinement.…”
Section: Introductionmentioning
confidence: 99%
“…In light of such strong relevance it is surprising that one of the simplest model systems of confined fluid -a non-polar molecular liquid confined between two atomically smooth surfaces -still evades full explanation. It is frequently reported that simple molecular liquids confined to films below 10 nm or so undergo a transition to solid-like behaviour (1,(7)(8)(9)(10)(11) however the nature of this transition continues to motivate discussion (12)(13)(14)(15). Furthermore, reported measurements of the shear stress sustained by these films span a wide spectrum with friction coefficients ranging from exceptionally low (for squalane (12)), through intermediate values (µ ∼0.1) for linear alkanes (16,17), and even much higher values (µ > 1) (8); all measured using similar apparatus employing a single-asperity contact.…”
mentioning
confidence: 99%
“…[41]). Future work using experimental setups that can track the composition of the fluid in the mica-mica slit [42] will shed light on whether the composition of the electrolyte changes abruptly as a function of bulk concentration.…”
mentioning
confidence: 99%